2016
DOI: 10.1111/pbi.12646
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a tomato miR171 target gene SlGRAS24 impacts multiple agronomical traits via regulating gibberellin and auxin homeostasis

Abstract: SummaryIn Arabidopsis, the miR171‐GRAS module has been clarified as key player in meristem maintenance. However, the knowledge about its role in fruit crops like tomato (Solanum lycopersicum) remains scarce. We previously identified tomato SlGRAS24 as a target gene of Sly‐miR171. To study the role of this probable transcription factor, we generated transgenic tomato plants underexpressing SlGRAS24, overexpressing SlGRAS24, overexpressing Sly‐miR171 and expressing β‐glucuronidase (GUS) under the SlGRAS24 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 53 publications
(78 reference statements)
6
92
0
Order By: Relevance
“…In contrast to the involvement of GRAS24 in the downstream signaling of GA (Huang et al ), GRAS2 likely functions in the upstream biosynthesis of GA. The differential roles of GRAS2 and GRAS24 in the GA pathway further illustrate the importance of GRAS genes for the stability of the GA pathway.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to the involvement of GRAS24 in the downstream signaling of GA (Huang et al ), GRAS2 likely functions in the upstream biosynthesis of GA. The differential roles of GRAS2 and GRAS24 in the GA pathway further illustrate the importance of GRAS genes for the stability of the GA pathway.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, DELLA , a negative regulator of GA signaling, was shown to restrain fruit growth (Marti et al ). In addition, GRAS24 regulates fruit development through modulating GA and auxin signaling (Huang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…8b). Interestingly, five of these miR-NAs (except miR397) have been demonstrated to be regulated by auxin signaling [35][36][37]. Moreover, a few Fig.…”
Section: Functional Analysis Of Duckweed Lncrnas Upon Salt Treatmentmentioning
confidence: 99%
“…GA is found to play important roles in many aspects of plant development such as oroan elonoation, oermination and flowerino time. It has been reported that expression of GRAS oenes in tomato showed dosedependent response to GA (Huang et al 2017). Our results demonstrated that the majority of CaGRAS oenes detected here displayed dramatic chanoes after GA treatment.…”
Section: Discussionsupporting
confidence: 73%